Functional Electrical Stimulation for Male Urinary Incontinence Management: A Systematic Review - Quetzal, Tracy (South East Asia Nursing Research, 2023)
Urinary incontinence (UI) is a prevalent condition among males, particularly following prostate surgery. Functional electrical stimulation (FES) has emerged as a potential therapy for managing this condition. This systematic review aims to evaluate the effectiveness of FES in the treatment of male urinary incontinence by synthesizing the available literature. A systematic search of electronic databases was conducted, identifying 15 studies that met the inclusion criteria. The results indicate that FES significantly improves continence rates and quality of life in males with urinary incontinence, particularly in post-prostatectomy patients. However, the variability in study design and patient populations highlights the need for further research to standardize treatment protocols.